Como crianças relatam seu desempenho acadêmico? estudo de correspondência fazer-dizer em situação escolar - Macchione, Ana Carolina Ceneviva (2012)
The expression correspondence between verbal and nonverbal behavior has been used to refer to the accuracy with which the individual reports what he did. Several studies have been conducted in this area, observing precisely the discriminative stimulus that should control the verbal response to later compare it with the verbal report. The present research aimed to investigate whether the manipulation of contingencies can affect the correspondence between doing and saying in a natural situation involving academic tasks; whether there is a relationship between the correction of the task made by the child and his or her history of success or error; and if the fact that the reporting behavior of the children occurs in a group affects the correspondence. To meet this objective, the children did exercises in the classroom given by the teacher and then, in another room, did the correction with the experimenter, who wrote the correct answers on the board where each child had to correct (mark right or wrong) their own exercise. After this correction, the child reported to the experimenter if he or she made the exercises correctly or not. Depending on the phase of the study, the child received tokens exchangeable for adhesives. In the Individual Baseline and Group Baseline phases, no contingency was planned for the reports; in the Group Reinforcement of the Correspondence and Individual Reinforcement of Correspondence, all correspondent reports were reinforced. Besides those, there was a Non-contingent Reinforcement session, in which the children won all the tokens and exchanged for the stickers before they started the report. During Individual Baseline sessions, it was observed that, in general, the number of correspondent reports was much greater than the non-correspondent reports, despite the significant number of the latter. Comparing this result to the group sessions, it can be observed that the number of error reports diminished substantially, increasing the number of non-correspondent reports of being right. For most participants, it was not possible to reverse the number of non-correspondent reports in the Reinforcement of Correspondence phases. The data from this research indicate that, in general, the different arrangements of reinforcement contingencies presented by the researcher were less effective in controlling the report than the contingencies involved in the groups in which the reports were made. Only a few participants seem to have been less affected by the presence of colleagues and more by the contingencies arranged by the experimenter. Moreover, when the participants were exposed to different experimental conditions, they had not only their report about academic tasks affected but also the corrections made by them